Mobile phone applications to screen for hearing loss in low-and middle-income countries: a state-of-the-art review - Abbey, Humphrey Kwaku (Department of Human Biology, 2022)
Hearing impairment is a chronic condition for which limited screening and diagnostic services are available in low-and-middle income countries (LMICs). In addition to the conventional medical devices existing to screen for the condition, several smartphone- and tablet-based applications have been introduced as mobile health (mHealth) solutions. This study was aimed at reviewing the set of mobile health tools available for screening for hearing loss in both developed countries and LMICs. Furthermore, to consider the suitability of the screening tools identified in the first objective for use in developing countries. The research approach adopted for this study was that of a state-of-the-art review. Relevant literature on mobile technology solutions to assess hearing loss were identified in electronic databases and reviewed. The mHealth solutions were reviewed with a focus on: countries of origin and evaluation; devices, software platforms and hardware considerations; hearing loss characteristics of recruited populations; features of the tests conducted and of the testing environment; reference methods to which the mobile application was compared; application performance; feedback from users; and cost. Eighteen available smartphone- and tablet-based applications for hearing loss screening were reviewed. Studies on these applications included participants from a variety of ages and, with and without hearing loss. A variety of testing environments were used. Studies on the applications found 11 of them to have acceptable functionality for use in screening for hearing loss. These 11 applications are also potentially suitable for use in LMICs, although they have some limitations. While these applications are not able to replace the conventional audiometer, they have potential as a first point of access for referral to conventional audiometry, and to help increase access to hearing loss tests in resource-constrained health systems.